2012
DOI: 10.1103/physrevlett.109.196803
|View full text |Cite
|
Sign up to set email alerts
|

Role of Percolation in the Conductance of Electrolyte-GatedSrTiO3

Abstract: We study the electrolyte-gate-induced conductance at the surface of SrTiO(3)(001). We find two distinct transport regimes as a function of gate voltage. At high carrier densities, a percolative metallic state is induced in which, at low temperatures, clear signatures of a Kondo effect are observed. At lower carrier densities, the resistance diverges at low temperatures and can be well described by a 2D variable range hopping model. We postulate that this derives from nonpercolative transport due to inhomogeneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
71
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 30 publications
14
71
1
Order By: Relevance
“…An upturn and saturation in the low temperature resistivity as shown in Fig. 4(b) was previously reported in electrolyte-gated STO, associated to the Kondo effect from local Ti 3þ magnetic moments [20,51]. However, as shown in Fig.…”
supporting
confidence: 68%
“…An upturn and saturation in the low temperature resistivity as shown in Fig. 4(b) was previously reported in electrolyte-gated STO, associated to the Kondo effect from local Ti 3þ magnetic moments [20,51]. However, as shown in Fig.…”
supporting
confidence: 68%
“…19). Indeed, evidence for such scattering is found from the Kondo effect observed in 2DEGs formed at the surface of STO single crystals when electrolyte gated 20,21 and the observation of magnetism at the LAO/STO interface [22][23][24] , which have both been attributed to the formation of Ti 3 þ magnetic centres 20,21,25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the dephasing rate clearly does not extrapolate to zero at zero temperature, suggesting a temperature-independent source of dephasing in our device, possibly local magnetic moments. Previous studies of EDLT-STO systems have shown Kondo effect at n > 6 * 10 13 with T K > 10 K [7,21]. At our lower carrier density, we might expect much lower T K , so our entire experimental temperature range could be T K , a regime in which magnetic impurities are predicted [22,23] and experimentally demonstrated [24,25] to yield constant-in-temperature dephasing.…”
mentioning
confidence: 98%